The RNA-Binding Protein NELFE Promotes Gastric Cancer Growth and Metastasis Through E2F2 - Chen, Changyu; Zheng, Qiang; Pan, Shubo; Chen, Wenzheng; Huang, Jianfeng; Cao, Yi; Tu, Yi; Li, Zhengrong; Yu, Changjun; Jie, Zhigang (Frontiers in Oncology, 2021)
Worldwide, the incidence rate of gastric cancer ranks fifth, and the mortality rate of gastric cancer ranks third among all malignant tumors. However, the pathogenesis of gastric cancer remains poorly understood. In this study, we demonstrated that the expression level of NELFE is higher in human gastric cancer tissues than in adjacent nontumor tissues. A high level of NELFE is associated with worse postoperative overall survival (OS) and relapse-free survival (RFS) rates in patients with gastric cancer. Moreover, the expression of NELFE is correlated with high tumor grade and lymph node metastasis in gastric cancer patients. Knockdown of NELFE dramatically inhibits the cell proliferation and metastasis of gastric cancer xenografts in vivo. Furthermore, we found that NELFE binding to the 3'UTR of E2F2 affects the mRNA stability of E2F2 to regulate the expression level of E2F2. In gastric cancer, E2F2 also acts as an oncogene to inhibit the proliferation and migration of gastric cancer cells by knocking down the expression level of E2F2. However, overexpressing E2F2 in cells with NELFE knockdown significantly reverses the inhibition of cell proliferation and migration induced by NELFE knockdown. Therefore, NELFE at least partially functions as an oncogene through E2F2. Moreover, CIBERSORT analysis of the proportion of tumor-infiltrating immune cells (TICs) revealed that immune cells are correlated with NELFE and E2F2 expression, suggesting that NELFE and E2F2 might be responsible for the preservation of the immunodominant status for gastric cancer. In conclusion, NELFE acts as an oncogene in gastric cancer and can be used as a potential therapeutic target.